2016
DOI: 10.1002/2016gl068279
|View full text |Cite
|
Sign up to set email alerts
|

Energetic particle precipitation: A major driver of the ozone budget in the Antarctic upper stratosphere

Abstract: Geomagnetic activity is thought to affect ozone and, possibly, climate in polar regions via energetic particle precipitation (EPP) but observational evidence of its importance in the seasonal stratospheric ozone variation on long time scales is still lacking. Here we fill this gap by showing that at high southern latitudes, late winter ozone series, covering the 1979–2014 period, exhibit an average stratospheric depletion of about 10–15% on a monthly basis caused by EPP. Daily observations indicate that every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(70 citation statements)
references
References 47 publications
11
59
0
Order By: Relevance
“…A clear negative downwelling signal of 5-30 % is observed in Antarctic winter 2003 from the lower mesosphere (≈ 0.3 hPa) in mid-winter to the lower stratosphere (below 10 hPa) in spring, preceded by a weaker (5-10 %) positive signal. The structure and strengths of this signal are similar to the downwelling anomalies derived from global satellite observations for the Southern Hemisphere (Fytterer et al, 2015a;Damiani et al, 2016) when comparing composites of years with high minus low geomagnetic activity, and are interpreted as particle impacts there. In the Northern Hemisphere, a similar negative downwelling signal starts in the lower mesosphere in early winter [2003][2004], but is interrupted by a strong (> 40 %) positive anomaly in late 2003 and early 2004 that is probably related to the onset of the sudden stratospheric warming.…”
Section: Comparison Of Modeled and Observed Ozone Anomaliessupporting
confidence: 64%
See 2 more Smart Citations
“…A clear negative downwelling signal of 5-30 % is observed in Antarctic winter 2003 from the lower mesosphere (≈ 0.3 hPa) in mid-winter to the lower stratosphere (below 10 hPa) in spring, preceded by a weaker (5-10 %) positive signal. The structure and strengths of this signal are similar to the downwelling anomalies derived from global satellite observations for the Southern Hemisphere (Fytterer et al, 2015a;Damiani et al, 2016) when comparing composites of years with high minus low geomagnetic activity, and are interpreted as particle impacts there. In the Northern Hemisphere, a similar negative downwelling signal starts in the lower mesosphere in early winter [2003][2004], but is interrupted by a strong (> 40 %) positive anomaly in late 2003 and early 2004 that is probably related to the onset of the sudden stratospheric warming.…”
Section: Comparison Of Modeled and Observed Ozone Anomaliessupporting
confidence: 64%
“…Previous studies based on observations have compared observations of ozone in situations with and without elevated amounts of NO y on the same day and in the same latitude range (Natarajan et al, 2004), the evolution of ozone in years with high energetic particle fluxes compared to years with low particle fluxes (Randall et al, 2005), and the composite difference of years with high minus years with low particle fluxes (Fytterer et al, 2015a;Damiani et al, 2016). All methods have yielded lower values of ozone in the upper stratosphere presumably related to the energetic particle precipitation; the composite method also shows negative ozone anomalies proceeding downwards from the stratopause to the mid-stratosphere during polar winter.…”
Section: Comparison Of Modeled and Observed Ozone Anomaliesmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been postulated already by Solomon et al (1982) and observed many times (Callis et al, 1996;Stratospheric ozone loss due to electron-induced NO x production in the upper mesosphere-lower thermosphere and subsequent downward transport has been postulated by model experiments many times (Solomon et al, 1982;Schmidt et al, 2006;Marsh et al, 2007;Baumgaertner et al, 2009;Reddmann et al, 2010;Semeniuk et al, 2011;Rozanov et al, 2012). However, observational evidence for EPP-induced variations of stratospheric ozone linked to geomagnetic activity, characterized by a negative anomaly moving down with time during polar winter, have been given only very recently (Fytterer et al, 2015a;Damiani et al, 2016).…”
Section: Geomagnetic Forcing (Auroral and Radiation Belt Electrons)mentioning
confidence: 92%
“…Only recently have long-term satellite observations with good temporal and spatial coverage become available. In austral polar winter EPP causes an ozone loss of about 10-15 % descending from 1 hPa in early winter to 10 hPa in late winter (Fytterer et al, 2015;Damiani et al, 2016). Extensive information on the current knowledge of energetic particle precipitation can be found in Sinnhuber et al (2012) and Mironova et al (2015).…”
Section: Introductionmentioning
confidence: 99%